Pengetahuan Dan Kecemasan Masyarakat Tentang Covid -19 - Kristianus triaspodo; Rizky Meilando; Kgs Muhammad Faizal (Institut Citra Internasional, 2021)
The continuous increase in COVID-19 data can cause public anxiety to increase. News circulating in society today, Covid-19 greatly affects their lives, this is what makes people anxious. This study finds out about people's knowledge and anxiety about COVID-19. This study uses an analytical survey method with a cross-sectional approach, the sample is taken from representatives of the people of Bangka Belitung who fill in the link totaling 275 people and the data is analyzed using the chi-square statistical test. The results of this study were 31.3% experienced anxiety, and there was a relationship between knowledge and anxiety as evidenced by the p-value of 0.00. In conclusion, there are many factors that cause anxiety, one of which is the news that is heard and seen by the public. Suggestions to be able to filter the news again with the knowledge possessed so that anxiety can be minimized.